Human Subperitoneal Fibroblast and Cancer Cell Interaction Creates Microenvironment That Enhances Tumor Progression and Metastasis - Kojima, Motohiro (Public Library of Science, 2014)
BACKGROUNDS: Peritoneal invasion in colon cancer is an important prognostic factor. Peritoneal invasion can be objectively identified as periotoneal elastic laminal invasion (ELI) by using elastica stain, and the cancer microenvironment formed by the peritoneal invasion (CMPI) can also be observed. Cases with ELI more frequently show distant metastasis and recurrence. Therefore, CMPI may represent a particular milieu that facilitates tumor progression. Pathological and biological investigations into CMPI may shed light on this possibly distinctive cancer microenvironment. METHODS: We analyzed area-specific tissue microarrays to determine the pathological features of CMPI, and propagated subperitoneal fibroblasts (SPFs) and submucosal fibroblasts (SMFs) from human colonic tissue. Biological characteristics and results of gene expression profile analyses were compared to better understand the peritoneal invasion of colon cancer and how this may form a special microenvironment through the interaction with SPFs. Mouse xenograft tumors, derived by co-injection of cancer cells with either SPFs or SMFs, were established to evaluate their active role on tumor progression and metastasis. RESULTS: We found that fibrosis with alpha smooth muscle actin (α-SMA) expression was a significant pathological feature of CMPI. The differences in proliferation and gene expression profile analyses suggested SPFs and SMFs were distinct populations, and that SPFs were characterized by a higher expressions of extracellular matrix (ECM)-associated genes. Furthermore, compared with SMFs, SPFs showed more variable alteration in gene expressions after cancer-cell-conditioned medium stimulation. Gene ontology analysis revealed that SPFs-specific upregulated genes were enriched by actin-binding or contractile-associated genes including α-SMA encoding ACTA2. Mouse xenograft tumors derived by co-injection of cancer cells with SPFs showed enhancement of tumor growth, metastasis, and capacity for tumor formation compared to those derived from co-injection with cancer cells and SMFs. CONCLUSIONS: CMPI is a special microenvironment, and interaction of SPFs and cancer cells within CMPI promote tumor growth and metastasis.